Apoptosis Induction by Lactobacillus casei Acidic Proteins in the Colorectal Cancer Cell Line - Mirzarazi, Mahsa; Bandehpour, Mojgan (Novelty in Biomedicine, 2022)
Background: Colorectal cancer (CRC) ranks third in cancer prevalence. Lactobacillus casei, a probiotic bacterium, can optimize the microbiota population of the gastrointestinal tract and prevent the growth of harmful bacteria that induce carcinogenesis. In this study, we investigated the effect of L. casei acidic proteins on apoptosis in the SW480 cell line to identify a drug protein for treating CRC. Materials and Methods: We assayed the effect of the isolated acid-resistant proteins of the Chaperonin bacterium, a metal-dependent Hydrolase, and Lysozyme on the SW480 colorectal cancer cell line apoptosis pathway gene expression with a Real-Time RT-PCR. Results: All three proteins induced apoptosis in the cells treated separately with each of the proteins. The results showed that the up-regulation of BAX and P53 gene expression and the apoptosis pathway were significantly induced. Also, BCL2 expression was down-regulated, and significant anti-apoptotic was observed at p<0.0001. Moreover, the cells treated with these three proteins down-regulated the expression of MAP2K1 and provoked the opposite apoptosis pathway. Conclusion: Our results found that these proteins would be a good choice for potential CRC treatment.